Sebuah Studi Analitis tentang Realitas Perilaku Oportunisme selama Musim Olahraga Profesional di Kalangan Atlet di Pusat Pengembangan Bakat Olahraga untuk Atletik. - Liqa Abdulzahra Obaid (Indonesian Journal of Physical Education and Sport Science, 2026)
Study purpose. With the growing professionalization of youth sport and the emergence of ethically problematic competitive behaviors, behavioral opportunism has become an urgent issue that lacks standardized measurement in sport psychology. Therefore, this study aimed to develop a psychometrically sound scale to measure behavioral opportunism during the professional sports season and to determine its level and key manifestations among track and field athletes at the Sports Talent Care Center. Materials and methods. A descriptive research design using the case study approach was employed. The research population consisted of 215 male athletes aged 15–17 years enrolled at the Sports Talent Care Center for track and field during the 2024/2025 sports season. The entire population was intentionally selected using a comprehensive enumeration method. The sample was divided into three groups: an exploratory sample, a construction sample (n = 109), and an application sample (n = 96). A behavioral opportunism scale was constructed based on four dimensions: careerism, self-centeredness, goal justification, and task hoarding. Validity and reliability were verified, and data were analyzed using the Statistical Package for the Social Sciences (SPSS). Results. The results indicated an unacceptable level of behavioral opportunism among athletes during the professional sports season. Athletes showed tendencies toward distorting facts, exploiting others’ weaknesses, exceeding ethical boundaries, justifying unethical means, and hoarding tasks and knowledge for personal benefit. Conclusions. Behavioral opportunism represents a critical psychological and ethical issue within the professionalization environment. Addressing it requires structured psychological preparation programs grounded in ethical values and strengthened collaboration with sport psychology specialists.